Collaborative leadership and school management committees' impact on primary teachers' job satisfaction in Sarawak, Malaysia. - Chang, Sze Phay; Roslee Talip (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2025)
This study investigates the relationship between headmasters' collaborative leadership, the role of School Management Committees (SMC), and teacher job satisfaction in Chinese National Type Schools (SJK(C)) in Sarawak, Malaysia. The aim is to explore how leadership styles and SMC involvement influence teacher satisfaction and improve the school environment. The study used a survey research design. Stratified, cluster, and simple random sampling were applied to select 120 teachers from 12 SJK(C) schools in Sarawak. Data were collected using questionnaires with Likert-scale items to measure headmasters' leadership, SMC roles, and teacher job satisfaction. The data analysis included descriptive statistics, factor analysis, and regression to examine relationships and mediation effects. The results showed that headmasters' collaborative leadership (β = 0.392) and SMC involvement (β = 0.327) had a positive and significant impact on teacher job satisfaction. The descriptive analysis indicated high satisfaction levels, with average scores of 4.21 for leadership, 3.76 for SMC roles, and 4.11 for teacher satisfaction. The findings confirmed that SMCs mediate the link between leadership and satisfaction, highlighting the importance of collaboration and support in schools. This study provides unique insights into how SMC involvement mediates the impact of collaborative leadership on teacher job satisfaction, focusing on Sarawak context that has not been widely studied. The study benefits school leaders, policymakers, and educators by highlighting effective leadership practices and the role of School Management Committees in improving teacher job satisfaction. It also supports better management and development strategies for rural schools.